The serological IgG and neutralizing antibody of SARS-CoV-2 omicron variant reinfection in Jiangsu Province, China - Chu, Jinjin; Dai, Qigang; Dong, Chen; Kong, Xiaoxiao; Tian, Hua; Li, Chuchu; Peng, Jiefu; Xu, Ke; Ju, Hao; Bao, Changjun; Hu, Jianli; Zhu, Liguo (Frontiers in Public Health, 2024)
Background: It is important to figure out the immunity of Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2) reinfection to understand the response of humans to viruses. A serological survey for previously infected populations in Jiangsu Province was conducted to compare the antibody level of SARS-CoV-2 in reinfection by Omicron or not. Methods: Reinfection with SARS-CoV-2 was defined as an individual being infected again after 90 days of the initial infection.Telephone surveys and face-to-face interviews were implemented to collect information.Experimental and control serum samples were collected from age-sex-matched reinfected and nonreinfected cases, respectively. IgG anti-S and neutralizing antibodies (Nab) concentrations were detected by the Magnetism Particulate Immunochemistry Luminescence Method (MCLIA). Antibody titers were log(2)-transformed and analyzed by a two-tailed Mann-Whitney U test. Subgroup analysis was conducted to explore the relationship between the strain type of primary infection, SARS-Cov-2 vaccination status, and antibody levels. Multivariate linear regression models were used to identify associations between reinfection with IgG and Nab levels. Results: 631 individuals were enrolled in this study, including 327 reinfected cases and 304 non-reinfected cases. The reinfection group had higher IgG (5.65 AU/mL vs 5.22 AU/mL) and Nab (8.02 AU/mL vs 7.25 AU/mL) levels compared to the non-reinfection group (P<0.001). Particularly, individuals who had received SARS-CoV-2 vaccination or were initially infected with the Wild type and Delta variant showed a significant increase in antibody levels after reinfection. After adjusting demographic variables, vaccination status and the type of primary infection together, IgG and Nab levels in the reinfected group increased by log(2)-transformed 0.71 and 0.64 units, respectively (P<0.001). This revealed that reinfection is an important factor that affects IgG and Nab levels in the population. Conclusions: Reinfection with Omicron in individuals previously infected with SARS-CoV-2 enhances IgG and Nab immune responses 1